2022
DOI: 10.12776/qip.v26i1.1612
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Influencing the Adoption of New Information Technology Supporting Healthy Life Style: The Example of Wearable Self-Tracking Devices

Abstract: Purpose: The presented study aims to identify key factors affecting the adoption of wearable electronics in Czech women. The results of the study can give insight on how to design an optimized wearable self-tracking device. Methodology/Approach: The well-established Unified Theory of Acceptance and Use of Technology (UTAUT) framework served as a baseline for research on key determinants of behavioral intention to use wearable self-tracking devices. Findings: The strongest factor was identified as the habit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Business analysis is carried out to measure or calculate whether a business will be successful [27]. Business analysis can also help solve company problems [28]. Product innovation is what can be considered as a functional product advancement that is one step ahead of competing products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Business analysis is carried out to measure or calculate whether a business will be successful [27]. Business analysis can also help solve company problems [28]. Product innovation is what can be considered as a functional product advancement that is one step ahead of competing products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevance of health motivation is obvious, because wearables are primarily used to monitor one's health and fitness factors. Consumers who have stronger health motivations or health beliefs are more likely to participate in the quantified-self movement via using wearables (Grosová et al, 2022;Paluch & Tuzovic, 2019;Zhang & Mao, 2022). Research has demonstrated the effects of health-related psychographic factors on one's exercise maintenance and subjective well-being (e.g., Mowen, 2000;Zhou & Krishnan, 2019).…”
Section: Motivational Antecedent: Health Motivationmentioning
confidence: 99%
“…There is a growing research interest surrounding wearable fitness devices, including the adoption and use (e.g., Kalantari, 2017;Grosová et al, 2022;Liu & Han, 2020), intermittent discontinuance (Shen et al, 2018), and continued use (Zhang & Mao, 2022). Studies have revealed the influencing factors such as perceived ease of use (e.g., Kim & Chiu, 2019), perceived usefulness (e.g., Cheung et al, 2021;Kim & Chiu, 2019;Felea et al, 2021), visibility -the extent to which a technology is apparent in the sense of sight of observable to others , and social influences -the effect of the social surroundings on individual consumers (e.g., Cheung et al, 2019).…”
mentioning
confidence: 99%